Toward a New Definition of Unmet Need for Contraception. Issue 2 (11th February 2019) - Rominski, Sarah D.; Stephenson, Rob
Abstract: The current definition of unmet need for contraception assumes that all women who are using a method have a met need. We argue that without taking into account the level of satisfaction with a method, many women are classified as having a met need, when in fact they have an unmet need. They are using a method that does not meet their preferences, either because it causes side effects they find untenable or has other characteristics they do not like. Given the large number of contraceptive episodes that end in discontinuation, reportedly often due to the experience of side effects, we argue that the current definition of unmet need undercounts the number of women with a true unmet need for contraception as it misses the many women who are using a method that does not meet their preferences. We suggest the addition of satisfaction questions in national surveys such as the Demographic and Health Surveys to more fully assess the level of true met need for contraception.